The formation of lenticular galaxies in nearby clusters - Johnston, Evelyn Joanne (2015)
Lenticular (S0) galaxies have long been thought of as evolved spirals, in which the star formation has been suppressed, the spiral arms have faded, and the luminosity of the bulge has been built up relative to the disc. However, the sequence of events that explains these three observations and leads to the formation of the final S0 galaxy is still uncertain. The progenitor spirals generally consist of bulges with old stellar populations surrounded by young, bright discs. Therefore, in order to explain the `quenching' of star formation in the disc and related increase in the bulge luminosity, an understanding of the individual star-formation histories of these two components is vital. In this thesis, we present a new technique to spectroscopically decompose the light from a galaxy into its bulge and disc components, from which the stellar populations and chemical compositions of the individual components can be extracted in order to determine the sequence of events leading to the transformation. Using spectroscopic bulge--disc decomposition, the spatial light profile in a two-dimensional galaxy spectrum can be separated wavelength-by-wavelength into bulge and disc components. This decomposition allows the construction of separate one-dimensional spectra representing purely the light from the bulge and disc, enabling studies of their individual star-formation histories with minimal contamination.This technique was applied to a sample of 30 S0s in the Virgo and Fornax Clusters, and analysis of the absorption line strengths within these spectra reveals that the bulges contain consistently younger and more metal-rich stellar populations than their surrounding discs. This result implies that the final episode of star formation before the progenitor spirals were fully quenched occurred in their central regions. Furthermore, the similarity in the alpha-element abundances of the bulges and discs indicates that the final episode of star formation in the bulge was fuelled using gas that has previously been chemically enriched in the disc. Together, these results present a picture in which the galaxy starts out as a typical spiral, with an old bulge surrounded by a young, star-forming disc. At some point in its life, gas is stripped from the galaxy, suppressing the star formation in the disc and causing the spiral arms to fade without inducing significant amounts of new star formation or disrupting the overall morphology of the galaxy. As the gas is removed, a fraction is also driven into the centre of the galaxy, where it fuels a final star-formation event in the bulge. This final episode of star formation consequently increases the luminosity of the bulge as the disc is already fading, and produces a central young, metal-rich stellar population. We have also shown that it is possible to spectroscopically decompose a galaxy using the different line-of-sight velocity distributions of kinematically distinct components. This technique was applied to NGC~4550, an unusual S0 galaxy in the Virgo Cluster with two counter-rotating stellar discs and a gaseous disc, to separate their individual stellar populations. Analysis of these stellar populations shows that the disc that co-rotates with the ionized gas is brighter and has a significantly younger mean age than the other disc, which are consistent with more recent star formation fuelled by the associated gaseous material. Therefore, the most likely formation mechanism for this galaxy is via an unusual gas accretion or merger scenario that built up a secondary stellar disc in a pre-existing S0 galaxy. The results presented in this thesis shed new light on the sequence of events that leads to the formation of S0 galaxies in cluster environments, and clearly demonstrates the importance of understanding the star-formation histories of the individual components within these galaxies in order to reconstruct the range of mechanisms by which they formed.